2023
DOI: 10.1007/s10529-023-03376-w
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cell-derived exosomes loaded with miR-26a through the novel immunomodulatory peptide DP7-C can promote osteogenesis

Shuang Lai,
Li Deng,
Cong Liu
et al.

Abstract: Purpose: As small bioactive molecules, exosomes can deliver osteogenesis-related miRNAs to target cells and promote osteogenesis. This study aimed to investigate miR-26a as a therapeutic cargo to be loaded into exosomes through a novel immunomodulatory peptide (DP7-C). In addition, the exosomes secreted from BMSCs were obtained to evaluate their osteogenic capacity.Methods: After transfecting BMSCs with DP7-C as a transfection agent, exosomes were extracted by ultracentrifugation from the culture supernatant o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…We attribute these therapeutic effects of complete hydrogel to the anti-inflammatory activity not only of azithromycin but also of BMSCs, which can dampen immune responses to spinal cord injury and mitigate the associated inflammatory damage. , In addition, BMSCs can differentiate into target cell types at the site of injury, promoting tissue repair and restoring tissue integrity. After BMSCs encapsulated TAT-AZM-NPs to form BMSCs-TAT-AZM-NPs, they enhanced the stability and sustained release of the drug delivery system, thereby enhancing the therapeutic efficacy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We attribute these therapeutic effects of complete hydrogel to the anti-inflammatory activity not only of azithromycin but also of BMSCs, which can dampen immune responses to spinal cord injury and mitigate the associated inflammatory damage. , In addition, BMSCs can differentiate into target cell types at the site of injury, promoting tissue repair and restoring tissue integrity. After BMSCs encapsulated TAT-AZM-NPs to form BMSCs-TAT-AZM-NPs, they enhanced the stability and sustained release of the drug delivery system, thereby enhancing the therapeutic efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…We attribute these therapeutic effects of complete hydrogel to the anti-inflammatory activity not only of azithromycin but also of BMSCs, which can dampen immune responses to spinal cord injury and mitigate the associated inflammatory damage. 43,44 In addition, BMSCs can differentiate into target cell types at the site…”
Section: Resultsmentioning
confidence: 99%
“…Similar to the activity of stem cells, MSCs-derived sEVs have been shown to reduce periodontal inflammation and enhance soft and hard tissue regeneration by regulating the expression of inflammation-related proteins and a range of signaling processes . Currently, several studies have reported that MSCs-derived sEVs can mediate periodontal inflammation by promoting periodontal cell proliferation and migration and down-regulating the expression level of apoptosis-related cytokines and form functional periodontal fibers that span the tooth root surface and new bone. In particular, BMMSCs-derived sEVs could regulate inflammatory response by influencing the polarization of macrophages through bone metabolism, prevent the development of periodontitis and the signaling pathways related to immune damage of periodontal tissue caused by inflammation, and then deliver osteogenesis-related miRNAs to target cells for improving the bone loss caused by periodontitis and promoting bone formation . Thus, loading BMMSCs-sEVs into the hydrogels described above can achieve the rapid repair of the periodontal tissue.…”
Section: Discussionmentioning
confidence: 99%
“…25−27 In particular, BMMSCs-derived sEVs could regulate inflammatory response by influencing the polarization of macrophages through bone metabolism, prevent the development of periodontitis and the signaling pathways related to immune damage of periodontal tissue caused by inflammation, and then deliver osteogenesis-related miRNAs to target cells for improving the bone loss caused by periodontitis and promoting bone formation. 61 Thus, loading BMMSCs-sEVs into the hydrogels described above can achieve the rapid repair of the periodontal tissue. Here, we successfully combined BMMSCs-sEVs with a thermosensitive antibacterial hydrogel loaded with oxygen-releasing particles benefiting from their antibiosis properties, thus synergistically promoting wound healing and restoring the complete structure and function of alveolar bone defects in periodontitis rats.…”
Section: Discussionmentioning
confidence: 99%
“…These functional modifications significantly improve bone regeneration through the exosomes, targeting the BMP2-associated signaling cascade/mTOR pathway. 199 , 200 Moreover, immune modifications performed by engineered exosomes also promote bone regeneration. Dendritic cell-derived exosomes loaded with IL-10 and TGF-β can inhibit immune-related bone resorption and suppress bone loss.…”
Section: Exosomes In Targeted Therapy For Oral Diseasesmentioning
confidence: 99%